Nutritional and therapeutic potential of Glycyrrhiza glabra L. roots - Hussain, Fatma; Iqbal, Irum (Asian Journal of Medical and Biological Research, 2020)
This study was aimed to estimate the antioxidant, anti-diabetic, anti-amnesic, anti-biofilm, thrombolytic, hemolytic, and cytotoxic effects of G. glabra root extracts for nutritive and medicinal purpose. Antioxidant, alpha amylase, antiglycation, anti-amnesic, cytotoxic, thrombolytic and antibiofilm assays were performed. In the current research, G. glabra root extracts showed significant antioxidant (80.96 mg GAE/100 g TPC, 38.96 mg CE/100 g TFC, 46% DPPH scavenging), antidiabetic (75% antiglycation, 38.7% α-amylase inhibition), anti-amnesic (5.5%), hemolytic (19.46%), thrombolytic (35.4%) and antibiofilm (72% P. multocida, 51.57% S. aureus inhibition) activities. G. glabra root extracts have remarkable activity to fight against oxidative stress, hyperglycemia, blood coagulation, bacterial growth, DNA damage and memory enhancing ability that ensure its uses in food and pharmaceutical industries. Asian J. Med. Biol. Res. June 2019, 5(4): 265-270